Kemampuan Pemecahan Masalah Matematika Ditinjau dari Disposisi Matematis pada Penerapan Model Pembelajaran Group Investigation (GI) - Islamiati, Nur; Lapele, Dina Amalya; Sari, Beatrix Purnama (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2021)
This study aims to describe how students 'problem-solving abilities in terms of students' mathematical dispositions on the application of the group investigation (GI) learning model. The approach used is qualitative and quantitative with descriptive types. The research subjects were 29 MAN 1 Malang class X. The data collection technique used a closed questionnaire type Likert scale, observation sheet and test questions. The results showed that learning using the group investigation learning model on mathematics learning could have a positive impact on the affective domain of students, namely mathematical disposition. The giving of the first and second disposition questionnaires increased by an average of 3.31 in the good category. Students' mathematical problem solving abilities based on mathematical dispositions are obtained by students with high dispositions who are able to solve problems properly and correctly. Students of moderate disposition can understand the problem well and provide solutions but are lacking in the solving process. Meanwhile, students with low mathematical disposition have less problem solving skills.